Instant noodle with fish meal inclusion (Research, Society and Development, 2021)
This work aimed to prepare an instant noodle with the inclusion of fish meal, evaluating the nutritional, microbiological and sensory quality. Four instant soups were developed, containing different fish flours (tilapia, smoked tilapia, smoked tilapia with salmon, and smoked tilapia with tuna). After the preparation of the flours, these were added to the soup ingredients, homogenized, packaged and analyzed for their nutritional and microbiological composition, then the soup was prepared with the addition of hot water for sensory analysis. All soup and fish meal mixtures were within microbiological standards for consumption. The soup mixture with inclusion of tilapia flour had higher moisture content and lower caloric value. Soups with smoked tilapia and smoked tilapia with salmon flour had the highest levels of lipids (6.90% and 6.89%, respectively) and smoked tilapia with tuna had the lowest ash content. There was no difference for protein and carbohydrates, as well as for the color and texture of soups. The mixture of instant soup with smoked tilapia flour with tuna had the worst acceptance in the aroma attribute. The taste, overall impression and purchase intent were worse for the soup with the inclusion of smoked tuna flour. It was concluded that instant soup mixtures enriched with fish meal are nutritious, with better acceptance for soups with tilapia, smoked tilapia and smoked tilapia with salmon meal.